Peru : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Peru's economic performance in 2012. The impressive growth is owed to its strong fundamentals and sound policy management. However, the economy is vulnerable to short-term shocks. A low growth in China or in the United States could hamper Peru's macroeconomic performance. The Executive Board has identified structural reforms for improving productivity, and recommends proactive use of macroprudential measures to limit financial vulnerabilities in the context of large capital inflows and strong credit growth.